Assessment of Pathogenic Potential of Avian Influenza Viruses by MDCK Cell Culture - Shankar, B.P.; Gowda, R. N. Sreenivas; Pattnaik, B.; Prabhu, B. H. Manjunatha; Kamal, R.P.; Sreenivas, B.K.; Madhusudhan, H.S.; Ranjith, D.; Pradhan, H.K. (International Journal of Poultry Science, 2009)
The influenza viruses are sub-classified in to two pathotypes of Highly Pathogenic Avian Influenza (HPAI) and Low Pathogenic Avian Influenza (LPAI) viruses on the basis of the pathogenicity of AIV in domestic poultry. Samples of H5N1 (7966/06 and 7972/06) and the H9N1 (5844/05) viruses were also grown on MDCK cell. All these produced cytopathic effect within 72 h. Normally, the nonpathogenic AIV does not produce CPE in MDCK cells. However, CPE can be produced if trypsin is incorporated while, culturing the viruses. In the present study, without the addition of trypsin the viruses produced CPE. On FAT both cytoplasmic and nuclear florescence was observed. It is also known that the viruses which produce CPE in absence of trypsin are pathogenic. It proved beyond that the H5N1 and H9N1 viruses isolated in the present study were pathogenic based on cell culture study.